Natural withanolides, an update. Issue 4 (24th November 2021) - Xia, Gui-yang; Cao, Shi-jie; Chen, Li-xia; Qiu, Feng
Abstract : This review summarizes the research progress on the structural classification, biological activities and mechanisms, metabolism and pharmacokinetic investigations, biosynthesis, and synthesis and structural modifications of the withanolides. Abstract : Covering: March 2010 to December 2020. Previous review: Nat. Prod. Rep., 2011, 28, 705 This review summarizes the latest progress and perspectives on the structural classification, biological activities and mechanisms, metabolism and pharmacokinetic investigations, biosynthesis, chemical synthesis and structural modifications, as well as future research directions of the promising natural withanolides. The literature from March 2010 to December 2020 is reviewed, and 287 references are cited.